Příjmy rozpočtů okresních úřadů - Pilný Jaroslav (Univerzita Pardubice, 1998)
The most significant revenues of district officies are those from taxes of physical persons. Revenues from this tax in budgets of three districts are balanced in years 1994-96. They fluctuated from 847 CZK to 1 004 CZK per one inhabiant in absolute value. However the income of this tax is 18 % under for the allstate average. Revenues from administrate fees fluctuated between 15-20 CZK per one inhabitant and they do not have significant influence among incomes of district offices. Revenues of district offices from the state budget are increasing while the incomes from physical person s taxes are falling down. For instance, in 1996 the revenue of District office Chrudim from taxes paid by physical persons per one inhabitant was 947 CZK and the revenues from state subsidies were 4 595 CZK. It means that there is a great second redistribution of finances which is not demanding or what is the evidence of not execellently determined budgest rules.
Keywords: okresní úřady; rozpočty; příjmy rozpočtu